Choroidal and macular thickness changes induced by cataract surgery - Falcão MS (Dove Medical Press, 2013)
Manuel S Falcão,1,2 Nuno M Gonçalves,2 Paulo Freitas-Costa,1,3 João B Beato,2 Amândio Rocha-Sousa,1,2 Ângela Carneiro,1,2 Elisete M Brandão,2 Fernando M Falcão-Reis1,21Department of Sense Organs, Faculty of Medicine, University of Porto, 2Department of Ophthalmology of Hospital de São João, 3Department of Anatomy, Faculty of Medicine, University of Porto, Porto, PortugalBackground: The aim of this study was to evaluate the effect of uneventful phacoemulsification on the morphology and thickness of the macula, the submacular choroid, and the peripapillary choroid.Methods: In 14 eyes from 14 patients, retinal macular thickness, choroidal submacular thickness, and choroidal peripapillary thickness were measured preoperatively and at one week and one month after phacoemulsification using enhanced depth imaging spectral domain optical coherence tomography. Changes in thickness of the different ocular tissues were evaluated.Results: There was a statistically significant increase in mean retinal macular thickness at one month. In horizontal scans, the mean increase was +8.67±6.75 µm (P<0.001), and in vertical scans, the mean increase was +8.80±7.07 µm (P=0.001). However, there were no significant changes in choroidal morphology in the submacular and peripapillary areas one month after surgery. In vertical scans, there was a nonsignificant increase in choroidal thickness (+4.21±20.2 µm; P=0.47) whilst in horizontal scans a nonsignificant decrease was recorded (−9.11±39.59 µm; P=0.41). In peripapillary scans, a nonsignificant increase in mean choroidal thickness was registered (+3.25±11.80 µm; P=0.36).Conclusion: Uncomplicated phacoemulsification induces nonpathologic increases in retinal macular thickness probably due to the inflammatory insult of the surgery; however these changes are not accompanied by significant changes in choroidal thickness. In the posterior segment, the morphologic response to the inflammatory insult of phacoemulsification is mainly observed at the retinal level, and seems to be independent of choroidal thickness changes.Keywords: phacoemulsification, macular thickness, choroidal thickness, prostaglandins